Seismic Expression of Polygonal Faults and Its Impact on Fluid Flow Migration for Gas Hydrates Formation in Deep Water of the South China Sea. (21st September 2011) - Chen, Duanxin; Wu, Shiguo; Wang, Xiujuan; Lv, Fuliang
Abstract : Polygonal faults were identified from three-dimensional (3D) seismic data in the middle-late Miocene marine sequences of the South China Sea. Polygonal faults in the study area are normal faults with fault lengths ranging from 100 to 1500 m, fault spaces ranging from 40 to 800 m, and throws ranging from 10 to 40 m. Gas hydrate was inferred from the seismic polarity, the reflection strength, and the temperature-pressure equilibrium computation results. Gas hydrates located in the sediments above the polygonal faults layer. Polygonal faults can act as pathways for the migration of fluid flow, which can supply hydrocarbons for the formation of gas hydrates.